Implementing block play: A strategic approach to optimizing critical thinking skills in early childhood education - Siti Aisyah; Erna Fauziah (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2026)
Background: While critical thinking skills are paramount in early childhood, conventional teacher-centered instructions often fail to provide optimal cognitive stimulation. Objective: This study to evaluate the effectiveness of structured block-play activities combined with strategic open-ended questioning in enhancing critical thinking skills among children aged 4–5. Method: Utilizing the Kemmis and McTaggart Classroom Action Research (CAR) model, this two-cycle study involved 10 participants (n=10) from Group A at PAUD Melati, Central Jakarta, with data collected via structured observations, semi-structured interviews, and artifact documentation over January–February 2026. The novelty of this study lies in its integration of structured block construction with systematic reflective prompts within an action research framework to transform passive play into active analytical reasoning. Result: Quantitative analysis revealed that the children's average classical critical thinking proficiency significantly increased from a baseline of 27.5% to 50.0% in Cycle I, and reached an optimal 81.25% in Cycle II, with independent problem-solving demonstrating the highest gain of 65%. Conclusion: In conclusion, structured block play serves as a highly effective pedagogical catalyst for fostering foundational higher-order thinking skills in early childhood education.